Potential to Increase Production and Income of Farmers of Freshwater Swamp Riceland in Gandus District, Palembang Regency - Yusni Novayanti; M Yamin (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Gandus District, Palembang Regency has 1,017.255 hectares of rice fields, most of which are spread in Pulokerto Village, which was a rice field with a freshwater swamp typology. Statistical data shows that rice productivity in Palembang Regency (4.4 tons/ha) was still low when compared to South Sumatra Province rice productivity (4.89 tons/ha) and national rice productivity (5.13 tons/ha). The writing of this article aimed to provide an overview of the potential for increasing the production and income of farmers in Gandus District, Palembang Regency. The potential for increased production can be analyzed by considering the productivity gap between rice productivity in Palembang Regency, provincial and national rice productivity, with intensification to increase productivity and increasing planting intensity to increase planted area. Agricultural intensification can be done through the use of superior seeds, proper fertilization, control of plant pests and diseases, and counseling to convey innovation and technology. Meanwhile, increasing cropping intensity by improving the irrigation system. With the increase in productivity and planting intensity, it can contribute to increasing the income and welfare of farmers in Pulokerto Village, Gandus District, Palembang Regency.